2009
DOI: 10.1128/jvi.00859-09
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-Specific Differences in the Human Immunodeficiency Virus Type 1 Reverse Transcriptase Connection Subdomain of CRF01_AE Are Associated with Higher Levels of Resistance to 3′-Azido-3′-Deoxythymidine

Abstract: We previously shown that mutations in the connection (CN) subdomain of human immunodeficiency virus type 1 (HIV-1) subtype B reverse transcriptase (RT) increase 3-azido-3-deoxythymidine (AZT) resistance in the context of thymidine analog mutations (TAMs) by affecting the balance between polymerization and RNase H activity. To determine whether this balance affects drug resistance in other HIV-1 subtypes, recombinant subtype CRF01_AE was analyzed. Interestingly, CRF01_AE containing TAMs exhibited 64-fold higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 47 publications
(62 reference statements)
2
38
0
Order By: Relevance
“…[23][24][25]30,34,[39][40][41] In this study, mutations in these portions were found in HIV-1B and C infecting patients under virological failure. Despite previous reports that have sporadically documented RT C-terminal mutations in non-B subtypes, 30,35,36 this is the first study specifically assessing differences of mutation occurrence in non-B subtype-specific contexts under the same therapeutic setting.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…[23][24][25]30,34,[39][40][41] In this study, mutations in these portions were found in HIV-1B and C infecting patients under virological failure. Despite previous reports that have sporadically documented RT C-terminal mutations in non-B subtypes, 30,35,36 this is the first study specifically assessing differences of mutation occurrence in non-B subtype-specific contexts under the same therapeutic setting.…”
Section: Discussionmentioning
confidence: 88%
“…43 This could indicate that treatment-naive isolates of Brazilian HIV-1C would take more time to acquire drug resistance to AZT-containing regimens. Notwithstanding, this polymorphism potentiates drug resistance conferred by TAMs in HIV-1B and CRF02_AG viruses, 35,36,43,44 and further studies are warranted to understand the impact of these changes on viral fitness.…”
Section: Novel Hiv-1 Rt C-terminal Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intersubtype recombinants in which epistatic pairs of mutations are separated from one another will thus have reduced fitness relative to either parent. It has also been shown that the polymorphism in the reverse transcriptase of the CRF-01_AE causes lower RNase H activity than that of NL4-3 subtype B viruses (13). Therefore, there may be inherent differences among proteins encoded by different subtypes.…”
Section: Vol 84 2010mentioning
confidence: 99%
“…We identified mutations in the CN from treatment-experienced patients that enhanced 3Ј-azido-3Ј-deoxythymidine (AZT) resistance (34,35), and closer examination of the CN and RH by us and others has identified additional mutations in this region that are associated with increased drug resistance (6,11,13,23,29,43,56,62). Several mutations in the CN of RT (N348I, T369I, and E399D) were identified by us and others to be associated with increases in both NRTI and NNRTI resistance (23,24,33,59).…”
mentioning
confidence: 99%